Walking on the tightrope: the shared roles of the bridging pericytes in the brain - Chagnot, Audrey; Montagne, Axel (Frontiers in Cellular Neuroscience, 2025)
The vasculature of the central nervous system (CNS) is a highly specialized structure that delivers oxygen and nutrients to energy-demanding neural cells while protecting them from the toxicity of blood-borne substances. Pericytes, located alongside microvessels, coordinate with endothelial cells to maintain the integrity of the blood-CNS barriers and to regulate vascular responses to neural activity. Pericytes extend processes that typically wrap around or align the endothelial cells, remaining embedded within the vascular basement membrane. Occasionally, however, some of these processes detach and form bridges between separate capillaries. These bridging structures are the focus of ongoing debate. While some studies propose they serve as tunneling nanotubes mediating neurovascular coupling, others argue they may be remnants of vascular regression or involved in the process of pericyte migration. In this review, we aim to clarify these varying interpretations of bridging pericyte processes and provide a unified understanding to guide future research. We discuss their reported roles in both CNS health and disease, highlighting their potential significance in vascular aging and rejuvenation.